THE ROLE OF DIGITAL TOOLS FOR LEARNING ENGLISH - Vakhobova Mukhlisa Khuvaydilla kizi; Bakhtiyorova Maftuna Bakhtiyorovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Digital tools have become essential in English language education, enhancing learning beyond traditional teacher-centered methods. Technologies such as online exercises, apps, video calls, and multimedia resources support all language skills, promote autonomous learning, and make lessons more interactive and engaging. Theories like constructivism, Communicative Language Teaching, and Multimedia Learning Theory explain how digital tools improve comprehension, retention, and practical language use. Scholars including Chapelle & Sauro, Levy, and Stockwell emphasize that, when used with clear pedagogical goals, technology can significantly enhance English learning.